Media Pembelajaran Ramah Lingkungan Sekolah Dasar Negeri Inklusi Di Pekanbaru Di Era Revolusi Industri 4.0 - Ahmad Denico (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2020)
The era of the industrial revolution 4.0 is famous for the rapid development of technology. This development must be accompanied by environmental balance. The development of technology that is not environmentally friendly becomes a problem for the community besides the problem of plastic waste which is equally disturbing. Environmental problems not only disturb society in general but also seeped into the educational environment for that, as educators, we must utilize used items to be used as learning media. This journal aims to determine the environmentally friendly learning media that can be used by teachers to deliver learning material that dances students in the class. An environmentally friendly learning media is a media that utilizes used goods to be used as a material delivery tool to focus on student learning. There are several environmentally friendly media that can be used by teachers including utilizing used bottles to be used as models for human breathing equipment, used boxes used as clock models, used aqua bottles used as transportation media models and others